Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 5 - Exponents and Polynomials - Chapter 5 Review Problem Set: 20

Answer

$-24x^3+3x^2$

Work Step by Step

RECALL: (i) $a^m \cdot a^n = a^{m+n}$ (ii) $a(b-c) = ab - ac$ Use the rules above to obtain: $=(-3x^2)(8x) - (-3x^2)(1) \\=-24x^{2+1} - (-3x^2) \\=-24x^3+3x^2$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.